Stereospecific analysis of major glycerolipids of Phycomyces blakesleeanus sporangiophores and mycelium. - DeBell, R M (1975)
The positional distribution of fatty acids was determined in the major groups of glycerolipids from the mycelium and sporangiophores of the fungus Phycomyces blakesleeanus. At the sn-1 positions of the triacylglycerols, in both regions of the fungus, greater than 65% of the fatty acids were 16:0 and 18:1. At the sn-2 positions of the triacylglycerols, 18:1, 18:2 and 18:3 comprised greater than 85% of the sporangial fatty acids and more than 90% of the mycelial fatty acids. Positions sn-3 of the triacylglycerols, from both regions of the fungus, contained approximately 40% of 16:0, approximately 30% of 18:2, and the largest proportions of 18:3 (21%) in the triacyglycerols. The major phosphoglycerides of P. blakesleeanus mycelium and sporangiophores are phosphatidylcholine and phosphatidylethanolamine, and more than 85% of the fatty acids at the sn-1 positions of these phosphatides consisted of 16:0, 18:2, and 18:3. The sn-2 positions of phosphatidylcholine and phosphatidylethanolamine contained approximately 98% unsaturated fatty acids. In the phosphoglycerides of both regions of the fungus, 18:2 and 18:3 constituted greater than 85% of the total fatty acids. Although the mycelium and sporangiophores of P. blakesleeanus had different morphological and physiological characteristics, the major glycerolipids of the two regions had similar stereospecific distributions of fatty acids.